Relationship between the mud organic matter content and the maximum height of diapiric domes using analog models - Ríos Reyes, Carlos Alberto; González Morales, Olivia; Rodríguez Madrid, Alfonso Luis; Ojeda Bueno, Germán Yury (CT&F - Ciencia, Tecnología y Futuro, 2015)
Mud diapirs are sedimentary structures produced by mud intrusion through a host rock. In this study, analog models of mud diapirism showed that gas generated from decomposition of organic matter contained in diapiric mud plays a fundamental role in the generation of these structures. This study is aimed to test the hypothesis that a relationship exists between the mud organic matter content (TOC) and the maximum height of diapiric domes. Our experiments were performed using sand boxes 20 x 20 x 16 cm in size, using nine mud combinations with TOC values that ranged between 1.6 and 4.3%, repeated 5 times to minimize random errors. Results of this study confirm that a linear relationship of the maximum height (mm) = 12.7xTOC (%) – 18.16 explains the elevations measured. In addition, an inverse linear relationship between TOC and the time at which the domes reached hmax was established. Observation of the morphological changes undergone by domes during their evolution allowed recognition of evolutionary stages that can be compared to the geomorphology of mud domes in nature. The relationships established in this study are useful to generate hypothesis about the organic matter content under active mud diapiric areas. For example, the elevations in the south of Colombia’s Sinú diapiric Belt (Abibe-Las Palomas Anticlinorium) are, on average, clearly higher than those in the northern part of this belt (Turbaco Anticlinorium). This may be the result of a much more organic-rich mud source under the southern Anticlinorium relative to the north. Finally, a warning is made on the risks of constructions above areas where mud diapirism occurs, which can be affected by the collapse of diapiric domes.